Hope for Our Technological Inheritance? From Substantive Critiques of Technology to Marcuse’s Post-Technological Rationality - Vieta, Marcelo (Strategies of Critique, 2021)
This paper explores the promise that Herbert Marcuse found in late modernity’s technological inheritance—his “other side” to his critique of technological rationality. With the goal of beginning to recover Marcuse’s desire for technological reform and a more hopeful project for a contemporary critical philosophy of technology, the paper first situates and contrasts Marcuse’s double-sided critique of technological rationality with the mostly negative critiques of modern technology exemplified by Heidegger, Adorno, and Horkheimer. Rather than offer concrete possibilities for socio-technical transformation, Heidegger, Adorno, and Horkheimer’s pessimistic views of technology tend to lead towards resignation in our late-modern fate. The paper then meditates on Marcuse’s “ambivalence theory of technology”—the notion that technologies are neither neutral nor inherently deterministic but, rather, politically and socially inscribed and entangled within webs of social struggles where their designed intentions are worked out and often reappropriated in actual use by users. The paper then looks at how Marcuse’s ambivalence theory can help in understanding the possibilities for re-valuing the technological base of advanced capitalist society within re-materialized values of love, joy, refusal, and sensuousness. Illustrating the continued relevance of Marcuse’s analysis for today’s radical left, the final section of the paper presents six key historical-conjunctural moments in Marcuse’s writings on technology that could be seen as prefiguring contemporary examples of technological reform and liberation from exploitative and alienating modes of life. Some of the newest social movements against neoliberal global capital, this final section argues, touch on elements of Marcusean-like re-rationalized and re-sensualized technological and organizational transformations.